Parasites in a wild white-tailed deer from Cajamarca, Peru - Murga-Moreno, César A. (2023)
In the present study, findings regarding parasites discovered in a white-tailed deer, Odocoileus virginianus peruvianus, captured in the dry forest of the Paccha district, Chota province, Cajamarca department, are reported. The Servicio Nacional Forestal y de Fauna Silvestre recovered parasites from an adult male specimen and forwarded them to the Tropical Medicine Research Center at the Universidad Nacional de Cajamarca for taxonomic identification of helminths and arthropods, as well as coproparasitological analysis. Two metacestodes corresponding to Cysticercus tenuicollis were identified. Qualitative coproparasitological analyses revealed Nematodirus spp. eggs at a concentration of 10 eggs per gram of feces (EPG) and 40 EPG of Strongylid type that could not be differentiated due to low counts in the coproculture. No trematode eggs were detected in the sedimentation. Among ectoparasites, eight hard ticks Rhipicephalus (Boophilus) microplus and five sucking lice Solenopotes binipilosus were identified. Several specimens were deposited in the Museo de Historia Natural de la Universidad Nacional Mayor de San Marcos, Lima. These findings represent the first formal report of the common cattle tick in this subspecies of cervid. Additionally, the presence of the Solenopotes binipilosus louse in Peruvian territory is reported for the first time.